Implikasi yuridis putusan Mahkamah Konstitusi nomor 93/PUU-X/2012 terkait dengan penyelesaian sengketa perbankan syariah - Dhaniar Eka Budiastanti (Jurnal Cakrawala Hukum, 2020)
Islamic Banking dispute resolution is an effort to resolve the problem carried out by the bank and the customer, if one of the parties is in default. The settlement of the Sharia Banking dispute is based on Law Number 21 of 2008 concerning Sharia Banking, particularly Article 55 of the Law. After the Constitutional Court gave its decision, through the Constitutional Court's Decision Number 93 / PUU-X / 2012, a legal implication occurred, namely the blurring of norms related to the resolution of Sharia Banking disputes. The writing method used is normative juridical, using the statutory approach (Statue Approach) and case approach. The results obtained related to this writing are the creation of a legal uncertainty related to the resolution of disputes outside the court (non-litigation).How to cite item: Budiastanti, D. (2020). Implikasi yuridis putusan Mahkamah Konstitusi nomor 93/PUU-X/2012 terkait dengan penyelesaian sengketa perbankan syariah. Jurnal Cakrawala Hukum, 11(1), 1-11. doi:https://doi.org/10.26905/idjch.v11i1.4120